Identification of insulin‐like growth factor 2 mRNA‐binding protein 3 as a radioresistance factor in squamous esophageal cancer cells. Issue 5 (18th September 2012) - Yoshino, K.; Motoyama, S.; Koyota, S.; Shibuya, K.; Sato, Y.; Sasaki, T.; Wakita, A.; Saito, H.; Minamiya, Y.; Sugiyama, T.; Ogawa, J.
Summary Identification of reliable markers of radiosensitivity and the key molecules that donate susceptibility to anticancer treatments to esophageal cancer cells would be highly desirable. We found that the mRNA expression of insulin‐like growth factor 2 mRNA‐binding protein 3 (IGF2BP3) was higher in radioresistant TE‐5 and TE‐9 cells than in radiosensitive TE‐12 cloneA1 cells. Conversely, knocking down expression of IGF2BP3 mRNA in TE‐5 and TE‐9 cells using small interfering RNA significantly enhanced their radiosensitivity. Furthermore, patients with squamous cell esophageal cancers strongly expressing IGF2BP3 tended to respond poorly to chemoradiation. These data suggest that IGF2BP3 may be a key marker of radiosensitivity that diminishes the susceptibility of squamous cell esophageal cancer cells to radiotherapy. IGF2BP3 may, thus, be a useful target for improving radiotherapy for patients with esophageal squamous cell carcinoma.